Modelling of roster : optimization of DEM roster at SGH - Yap, Wei Qing. (2009)
A rise in standard of living in Singapore has led to an increase of healthcare awareness among people. This trend is in fact keeping healthcare centers busier than before. Therefore, there is a need to maintain high efficiency in healthcare centre at the same time ensuring that the staffs are still leading a balance and healthy working lifestyle. In this project, the author got the chance to work together with Singhealth and Department of Emergency (DEM) in Singapore General Hospital (SGH). Singhealth had studied that the current DEM (Department of Emergency) roster needs to be improved in terms of ease of planning and efficiency. Operation research technique was employed to carry out this project. Firstly, the process flow of the DEM roster was mapped out. The problem was later looked upon as an assignment problem and linear programming method was used to tackle the problem. The objectives of the problem were first identified. Later on, the constraints and conditions attached to the problem were analyzed as well. Finally, they were being converted to mathematical equations. These equations were input into spreadsheets which formed the model. Basic solver was used at the beginning stage to test out the roster’s feasibility. Later on, risk solver which is a more advanced software was used to complete the model. The solutions were reviewed at the end after the model had been solved. They met most of the constraints and requirements that DEM wants. However, the author feels that the model can work better on a larger scale advanced solver where unlimited decision variables can be used. An improved version of the new model using advanced solver could be much more desirable than the current DEM roster that the doctors are using.